LAYANAN KONSELING KELOMPOK DALAM MENINGKATKAN PSYCHOLOGICAL WELL-BEING REMAJA DI LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) PANGKALPINANG - Paramitha, Siska Dwi (Scientia: Jurnal Hasil Penelitian, 2019)
Psychological well-being is needed by every individual. Psychological services are needed to achieve prosperity in psychology, one of which is group counseling services. In this case, adolescents who are in the Special Correctional Institution for Child (Lembaga Pembinaan Khusus Anak, LPKA) need to improve psychological well-being which hopes of being able to return to their role and get good acceptance in the community or social environment. This research is experimental research by a pre-experimental design-one group pretest-posttest design. The treatment given in the form of group counseling services and given questionnaires before and after treatment was given. There were 17 subjects in which group counseling services had never been done before at LPKA. Data analysis used the t-test and Gain Score. The results showed the psychological well-being of adolescents significantly no increase given to group counseling services. But, if you see the gain score data, it was found that 7 of 17 subjects experienced an increase before and after being given group counseling services.